Optimizing the social utility of judicial punishment: An evolutionary biology and neuroscience perspective - Levy, Daniel A. (Frontiers in Human Neuroscience, 2022)
Punishment as a response to impairment of individual or group welfare may be found not only among humans but also among a wide range of social animals. In some cases, acts of punishment serve to increase social cooperation among conspecifics. Such phenomena motivate the search for the biological foundations of punishment among humans. Of special interest are cases of pro-social punishment of individuals harming others. Behavioral studies have shown that in economic games people punish exploiters even at a cost to their own welfare. Additionally, neuroimaging studies have reported activity during the planning of such punishment in brain areas involved in the anticipation of reward. Such findings hint that there is an evolutionarily honed basic drive to punish social offenders. I argue that the transfer of punishment authority from the individual to the group requires that social offenders be punished as a public good, even if such punishment is not effective as retribution or deterrent. Furthermore, the social need for punishment of offenders has implications for alternatives to incarceration, publicity of punishment, and judicial structure.